2014
DOI: 10.1111/vop.12175
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic diagnostic tests in captive red‐footed tortoises (Chelonoidis carbonaria) in Salvador, northeast Brazil

Abstract: In both seasons, Gram-positive bacteria were predominant. Median (± IQR/2) STT was 12.0 ± 3.5 mm/min, EAPPTT-1 was 15.9 ± 0.7 mm/15 s, and EAPPTT-2 was 15.4 ± 0.4 mm/min (OD) and 17.8 ± 1.0 mm/min (OS). Anterior chamber depth was 1.0 ± 0.1 mm, lens axial length was 2.3 ± 0.1 mm, vitreous chamber depth was 4.3 ± 0.2 mm, and axial globe length was 7.7 ± 0.3 mm. PFL was 11.7 ± 1.7 mm. Intraocular pressure was 11.5 ± 2.8 mmHg for males and 14.0 ± 3.5 mmHg for females (dorsoventral position) and 18.0 ± 3.2 mmHg for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…Previous studies in sea turtles have reported conjunctival bacterial flora in sick animals . The mostly bacterial isolated of chelonians and other ectothermic animals are classified as mesophilic and its optimal temperature for growth is 25‐40°C, similar to the present study. However, there are no such studies on healthy sea turtles in free life or under human care nor any description of the antimicrobial susceptibility of their microflora.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Previous studies in sea turtles have reported conjunctival bacterial flora in sick animals . The mostly bacterial isolated of chelonians and other ectothermic animals are classified as mesophilic and its optimal temperature for growth is 25‐40°C, similar to the present study. However, there are no such studies on healthy sea turtles in free life or under human care nor any description of the antimicrobial susceptibility of their microflora.…”
Section: Discussionsupporting
confidence: 86%
“…Most conjunctival culture samples in this study showed bacterial growth, as reported for Chelonoides carbonaria and Trachemys scripta elegans . The greatest number of isolates was found in Chelonia mydas and Eretmochelys imbricata , both from visitor center.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Ophthalmology is becoming an essential specialty for maintaining healthy eyes in wild animals and exotic species . However, basic studies on eye physiology in some species of wild animals, especially those from South America, are still incipient, and baseline values for primates are particularly lacking .…”
Section: Introductionmentioning
confidence: 99%